Suspected piperacillin‐tazobactam induced nephrotoxicity in the pediatric oncology population. Issue 2 (30th August 2013) - Pratt, Jennifer A.; Stricherz, Melisa K.; Verghese, Priya S.; Burke, Michael J.
Abstract Neutropenic fever is a common complication of myelosuppressive therapy in pediatric oncology patients. Piperacillin‐tazobactam (PIP/TAZO) is a broad spectrum antibiotic used for empiric treatment of neutropenic fever. We describe four cases of suspected PIP/TAZO induced nephrotoxicity occurring in children with pediatric malignancies admitted to the hospital and treated for fever ± neutropenia. All patients exhibited acute renal injury shortly after PIP/TAZO administration with one of these cases having biopsy evidence of acute interstitial nephritis. These findings are suggestive of PIP/TAZO induced nephrotoxicity in pediatric oncology patients with fever ± neutropenia and that PIP/TAZO should be used judiciously in this population. Pediatr Blood Cancer 2014;61:366–368. © 2013 Wiley Periodicals, Inc.